Perception of individual and group discrimination among LGB individuals in Puerto Rico: A descriptive study - Caleb Esteban; Juan Aníbal González-Rivera (Interacciones)
Background: Discrimination is one or more unjustified negative behaviors towards a person based on one or more characteristics of that person. In the case of lesbian, gay, and bisexual (LGB) persons, they have been constant victims of stereotypes, prejudices, and discrimination around the world. However, few scientific studies explore the experiences of discrimination in Puerto Rico, since most studies have focused on negative attitudes, prejudice, and social distance. Objective: The aims of this brief report are 1) to describe in detail the relative importance of the quality of the items of the Perceived Discrimination in the LGB Community Scale, and 2) to describe the experiences of discrimination both at the individual and group level of an LGB sample according to the order of relative importance found. Method: This research had a quantitative method with a descriptive study design, instrumental type. To meet the objective of this study, the data collected in each item was independently evaluated to examine the experience and perception of each participant in the situation presented by each premise. A non-probability sample of 300 LGB participants was recruited in Puerto Rico. Results: The area with the highest reported experiences of individual discrimination was the relationship category (M=.700), followed by psychological (M=.630), society/environmental (M=.566), family/employment (M=.566) and physical (M=.386) respectively. The area with the highest perceptions of group discrimination reported by the sample was the education/health category (M = .882), followed by culture/society (M=.827), politics (M=.803), maternity/paternity (M=.802) and locality (M=.791) respectively. Conclusion: When analyzing all the items, it was observed that the results of the first 22 positions according to the Relative Importance Index, correspond to the experiences of discrimination in a group way. This means that people perceive greater discrimination as a group than the discrimination they perceive about their own person.